Potential New Applications of Sodium–Glucose Cotransporter-2 Inhibitors Across the Continuum of Cancer-Related Cardiovascular Toxicity - Agnieszka Maria Zebrowska; Anna Borowiec (Pharmaceuticals)
Sodium–glucose cotransporter-2 inhibitors (SGLT2i), initially developed for the management of type 2 diabetes mellitus, have demonstrated significant nephroprotective and cardioprotective effects. These benefits have led to their inclusion in heart failure (HF) management guidelines, irrespective of glycemic status and left ventricular ejection fraction (LVEF). Various anticancer therapies, particularly anthracyclines, are associated with substantial cardiotoxicity risks, resulting in cancer therapy-related cardiovascular toxicity (CTR-CVT). Promising evidence from preclinical and observational studies indicates that SGLT2i may mitigate cardiotoxic effects of cancer therapy by alleviating LVEF decline, reducing HF incidence and hospitalizations, and lowering overall mortality. Moreover, improved survival has been reported in patients with various malignancies. The current review explores the potential applications of SGLT2i in the prevention of CTR-CVT, highlights their possible mechanisms of cardioprotection, discusses the published evidence, and emphasizes the need for the results from ongoing randomized controlled trials to establish SGLT2i efficacy and safety in cardio-oncology patients.